KEMAMPUAN MENULIS KARANGAN DESKRIPSI EKSPOSITORIS SISWA KELAS X SMA NEGERI I SOLOK SELATAN DENGAN MENGGUNAKAN TEKNIK OBJEK LANGSUNG - Wati, Susi Widia; Mana, Lira Hayu Afdetis; Yulianti, Upit (Pendidikan Bahasa Indonesia, 2013)
This research is motivated by some problems. First, students are less interested in writing a description essay is one of the obstacles in writing skills. Second, students are difficult to develop ideas and ideas into the form of expository description. Third, students are less capable of displaying details of objects that have been observed, and difficult students describe something that can be seen, heard and felt. Fourth, students are less able to use that evocative word choice and writing descriptions by using the present arrangement of space. This type of quantitative research using descriptive methods. The study population was all students in the class X SMA N I South Solok in the year 2012/2013 amounted to 210 people scattered in the 8 th grade. Given a population of more than 100 students. it is necessary to recall the sample Samples taken 15 % of the student population that is 35 people. The data of this study in the form of writing descriptions of class X SMA N I South Solok using the techniques of the direct object .Based on the research and analysis of data, it can be seen that in general the ability to write an expository essay description class X SMA NI South Solok quite good ( 77.62 % ). Expository essay writing skills students can detailed description based on the indicators . First, the details of the objects classified as either once ( 86.68 ). Second, quite evocative word choice more than enough ( 73.74 ), Third, describes something that can be seen, heard and felt relatively less so ( 33.43 ). Fourth, using a spatial arrangement is fair at all ( 92.38 ). The conclusion of this research is the ability to write essays description ekspsositoris class X SMA NI South Solok using the technique of direct objects belonging to both the mastery 77.62 % are in the 76-85 range on a scale of 10. Based on the above conclusions, advised the following two things. First, to the Indonesian language and literature teachers should give more practice writing with a variety of learning techniques so that students are motivated to write a description of the particular writing expository essay. Second, students should gain knowledge about the concept of writing and reproduce writing exercises especially writing descriptions.